1986
DOI: 10.1159/000226353
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes in Malignant Melanoma: Serial Studies in 130 Patients

Abstract: We evaluated the ability of repeated measurements of circulating immune complexes (CIC) to predict for tumor recurrence in 130 patients with malignant melanoma. Twenty-two patients had level 2, 45 had level 3, and 51 had level 4/5, stage I disease in remission at the start of monitoring, while 12 had stage II disease. The polyethylene glycol precipitation assay was used for serial studies, based on an initial comparative evaluation with the Clq-binding and Raji assays. The study averaged 22 ± 11 months (6–43 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

1988
1988
1989
1989

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
5
2
Order By: Relevance
“…In previous serial studies, recurrence/progressive growth of malignant melanoma was reported to be associated with significant changes in clC levels [15], with raised clC levels [3,15,16], or with reduced clC levels [14]. In contrast to these findings, significant changes in clC and C3d levels, defined by reference to the changes that occurred in serial samples from healthy controls, were not associated with the development of recurrent disease in our 50 patients with malignant melanoma.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…In previous serial studies, recurrence/progressive growth of malignant melanoma was reported to be associated with significant changes in clC levels [15], with raised clC levels [3,15,16], or with reduced clC levels [14]. In contrast to these findings, significant changes in clC and C3d levels, defined by reference to the changes that occurred in serial samples from healthy controls, were not associated with the development of recurrent disease in our 50 patients with malignant melanoma.…”
Section: Discussioncontrasting
confidence: 70%
“…The usefulness of serial measurements of clC to predict recurrence of disease should, if possible, be evaluated in patients without known systemic dissemination of disease as in the presented study and in the studies of Bharwani et al [3], Ronai et al [14], and Ruell et al [16]. In the study of Rossen et al [15], 35 of the 53 melanoma patients had distant metastases when entering the study, and the conclusions therefore rely rather on progression than recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations